Assessment of Anti-inflammatory and Antioxidant Compounds in Gastrointestinal Digests From Germinated Amaranth Protein Concentrate. (14th June 2022) - Sandoval-Sicairos, Eslim; Montoya-Rodriguez, Alvaro; Antunes-Ricardo, Marilena; Luna-Vital, Diego; Milán-Carrillo, Jorge; Milán-Noris, Ada
Abstract: Objectives: Amaranth ( Amaranthus hypochondriacus ) is an ancestral nutritional grain with relevant nutritional value. The aim of this study was to evaluate the release of peptides and phenolics with antioxidant (AOX) and anti-inflammatory potential by simulated gastrointestinal digestion and absorption from a germinated amaranth protein concentrate (GAPC). Methods: The in vitro simulated protein digestion of GAPC was achieved by enzymatic hydrolysis with pepsin (90 min) followed by pancreatin (60 min). After digestion of GAPC, two digests were attained: the absorbable (GAPC-out) and non-absorbable (GAPC-in), both were further fractioned to F1(>10 kDa) and F2(< 10 kDa) by ultrafiltration. The anti-inflammatory potential was determinate as percentage of nitric oxide (NO) inhibition in lipopolysaccharide-induced in RAW 264.7 macrophages and the AOX potential was evaluated using the oxygen radical absorption capacity (ORAC) method. The peptide and phenolics digests fractions were analyzed by high-performance liquid chromatography-mass spectrometry. Results: The amaranth peptides from GAPC-in showed higher (p > 0.05) anti-inflammatory potential compared to GAPC-out. The NO inhibition percentages ranged from 42 to 87 by the assayed doses (0.25–1 mg/mL). Also, the F1 fraction presented higher NO inhibition percentages (p > 0.05) than F2 fraction from GAPC-in. Likewise, the phenolics in the GAPC-in digest showed better anti-inflammatory potential at 0.25–0.5 mg/mL doses (p > 0.05) than GAPC-out digest. Besides, the GAPC digestion increased 2.7-fold AOX (p > 0.05) compared to undigested GAPC. The GAPC-out digest showed higher AOX potential than GAPC-in digest. Moreover, in GAPC digests 18 peptides sequences were identified with potential health effect, whereas methyl gallate and syringic acid were the main phenolic presented in both digests. Conclusions: Finally, this study highlighted the potential of the germinated amaranth protein concentrate as antioxidant and anti-inflammatory functional ingredient to the prevention of inflammatory intestinal diseases. Funding Sources: Conacyt and Profapi.